Design and Quality Analysis of Nara Sela Contemporary Fashion with QR Code Based Interactive Fashion - Nuzila Mar'a Jamila; Sri Endah Wahyuningsih (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
The development of the fashion industry in the digital age has encouraged the incorporation of interactive technology into contemporary fashion design. This study aims to (1) describe the design process of contemporary fashion of Nara Sela and (2) analyze its quality through the application of interactive features based on QR codes. The research uses the Research and Development (R&D) method using the PPE (Planning, Production, and Evaluation) development model. Data were collected through observation sheets involving five expert panelists and twenty trained panelists and analyzed using descriptive quantitative techniques. The results of the study show that 1) Nara Sela fashion design integrates QR codes as an integral design element rather than just serving as an information label. Digital content accessed through QR codes includes design concept narratives, fashion visuals, and photo and video documentation, which adds value by enhancing the user experience. 2) the results of the evaluation show that the quality of Nara Sela's fashion is categorized as very feasible based on aspects of design, aesthetics, sewing techniques, performance, and uniqueness. These findings have implications for the development of fashion education and digital fashion, particularly in promoting innovation in contemporary fashion that integrates aesthetic values with interactive user experiences.